2021
DOI: 10.31477/rjmf.202103.49
|View full text |Cite
|
Sign up to set email alerts
|

Probability of Default Model to Estimate Ex Ante Credit Risk

Abstract: A genuine measure of ex ante credit risk links borrower’s financial position with the odds of default. Comprehension of a borrower’s financial position is proxied by the derivatives of its filled financial statements, i.e., financial ratios. We identify statistically significant relationships between shortlisted financial ratios and subsequent default events and develop a probability of default (PD) model that assesses the likelihood of a borrower going into delinquency at a one-year horizon. We compare the PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
(33 reference statements)
1
0
0
Order By: Relevance
“…Additionally, it constructed a probability of default (PD) model to estimate the likelihood that a borrower will enter delinquency within a one-year timeframe. The study's findings revealed noteworthy associations between the two variables (Burova et al, 2021). Also, similar studies are performed using increased financial ratios and a greater pool of companies.…”
Section: Performance Assessment Using Financial Ratiossupporting
confidence: 51%
“…Additionally, it constructed a probability of default (PD) model to estimate the likelihood that a borrower will enter delinquency within a one-year timeframe. The study's findings revealed noteworthy associations between the two variables (Burova et al, 2021). Also, similar studies are performed using increased financial ratios and a greater pool of companies.…”
Section: Performance Assessment Using Financial Ratiossupporting
confidence: 51%